(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, the development of heavy industries in the southern regions of Uzbekistan, conflicting situations in the process of training industry personnel are analyzed historically based on scientific sources.